Eccentric versus traditional resistance exercise for older adult fallers in the community: a randomized trial within a multi-component fall reduction program - Paul LaStayo (BMC Geriatrics, 2017)
Abstract Background Addressing muscle deficits within a multi-component exercise fall reduction program is a priority, especially for the highest risk older adults, i.e., those who have fallen previously. Eccentric resistance exercise with its high-force producing potential, at a low energetic cost, may be ideally-suited to address muscle impairments in this population. The purpose of this study was to compare the effects of resistance exercise via negative, eccentrically-induced, work (RENEW) versus traditional (TRAD) resistance exercise on mobility, balance confidence, muscle power and cross sectional area, as well as the number of days high fall risk older adults survived without a fall event over a 1 year period. Methods Randomized, two group, four time point (over 1 year) clinical trial testing RENEW versus TRAD as part of a 3 month multi-component exercise fall reduction program (MCEFRP). Primary outcomes of mobility, balance confidence, muscle power output and cross sectional area were analyzed using mixed effects modeling. The secondary outcomes of days to fall and days to near-fall were analyzed using survival analysis. Results The MCEFRP did have an effect on fall risk factors considered reversible with exercise interventions though there was no differential effect of RENEW versus TRAD (p = 0.896) on mobility, balance confidence, muscle power and cross sectional area. There were also no group differences in the number of days survived without a fall (p = 0.565) or near-fall (p = 0.678). Despite 100% of participants having at least one fall in the year prior to the MCEFRP, however, after 3 months of exercise and 9 months of follow-up <50% had experienced a fall or near fall. Conclusions There were no differential effects of RENEW or TRAD as components of a MCEFRP on the primary or secondary outcomes. The two modes of resistance exercise had identical effects on fall risk and fall-free survival. Trial registration NCT01080196 ; March 2, 2010 (retrospectively registered).